Handgrip Based Action Information Modulates Attentional Selection: An ERP Study - Kumar, Sanjay; Riddoch, M. Jane; Humphreys, Glyn W. (Frontiers in Human Neuroscience, 2021)
Prior work shows that the possibility of action to an object (visual affordance) facilitates attentional deployment (e.g., see Humphreys et al., 2010). We sought to investigate the neural mechanisms underlying this modulation of attention by examining ERPs to target objects that were either congruently or incongruently gripped for their use in the presence of a congruently or incongruently gripped distractor. Participants responded to presence or absence of a target object matching a preceding action word with a distractor object presented in the opposite location. Participants were faster in responding to congruently gripped targets compared to incongruently gripped targets. There was a reduced N2pc potential when the target was congruently gripped, and the distractor was incongruently gripped compared to the conditions where targets were incongruently gripped or when the distractor as well as target was congruently gripped. The N2pc results indicate that target selection is easier when action information is congruent with an object’s use.